Measuring Adolescent HIV Self-management: An Instrument Development Study. - Crowley, Talitha; Van der Merwe, Anita; Kidd, Martin; Skinner, Donald (AIDS & Behavior, 2020)
Adolescent HIV self-management is a complex phenomenon that has been poorly researched. A mixed-method explorative sequential research design was used to develop an instrument to measure adolescent HIV self-management in the context of the Western Cape, South Africa. The development and validation was undertaken in four phases: (i) individual interviews and focus groups with adolescents aged 13 to 18, their caregivers and healthcare workers (n = 56); (ii) item identification; (iii) item refinement through cognitive interviewing (n = 11), expert review (n = 11) and pilot testing (n = 33); and (iv) psychometric evaluation (n = 385). The final scale consists of five components with 35 items encompassing the construct of adolescent HIV self-management. The developed scale had acceptable reliability (0.84) and stability (0.76). Factor analysis indicated a good model-fit that support the structural validity (RMSEA = 0.052, p = 0.24; RMR = 0.065; CFI = 0.9). Higher self-management was associated with better HIV-related and general health outcomes, which supports the criterion- and convergent validity of the instrument.